Relationship between shot efficiency, goalkeeper efficiency and the point's difference evolution in handball game - Volossovitch, A.; Ferreira, A. P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The use of modern objective and reliable computerised methods provides an exact and detailed record of performance in sport games. However, not all the obtained information is equally useful and significant for the evaluation of a players actions and their influence on the match result. As knows, the players may react differently to similar events when competing against different opponent and in different circumstances. The performance in sport games emerges from the context of the competition. This context is a result of the interaction between opposite teams, which is reflected in the score evolution in time. Every game has its own and unique dynamics. Our previous research showed that the summarised data are not sufficiently informative for explaining the teams success or failure in the even games (Volossovitch et al., 2003). Thus, to be valid, the assessment of performance should take into account a time location of players action and consider the opposition relationship between playing teams (Borrie et al., 2002; Lames, 2003). The purpose of our study was to compare the relationship of two most important game indicators: shot efficiency and goalkeeper efficiency with the score evolution in even games in Handball. Methods The sample consisted of five even games randomly selected from 84 games of 18th Mens World Championship of Handball. The Cluster analysis was applied in order to categorise the matches as even, uneven and very uneven, in function of two variables: the final points differences and the average of points differences per minute, which describe the score evolution in the match. The shot efficiency (number of shots/goal scored*100%) and goalkeeper efficiency (number of opposite shots/shots defended*100%) of winner and loser teams were calculated for each five minute of the match. The evaluation of points differences by 5 min (edp) was calculated using the equation: edp = dp2.dp1, where dp1 is a points difference registered in each 5 min period and dp2 is a points difference registered in the subsequent period of 5 min. The Spearman correlation coefficient was used for analysis of relationship between shot efficiency of winner/loser team, the goalkeeper efficiency of winner/loser teams and the points difference evolution in the game. Results The preliminary results proved a reliable positive correlation between goalkeeper efficiency of winner teams and the points difference evolution in two from five analyzed games (r=0,642 p.0.05 and r=0,607, p.0.05). In one game the positive correlation was registered between shot efficiency of winner team and the points difference evolution (r=0,798, p.0.01). It was noted a reliable negative correlation between shot efficiency of loser teams and points difference evolution in three cases (r=-0,588, p.0.05; r=-0,686, p.0.05 and r=-610, p.0.05) and in one case the goalkeeper efficiency was significantly negatively related with points difference evolution (r=-0,916, p.0.01). Discussion/Conclusion The results suggested that in case of winner teams the increase of goalkeeper efficiency is accompanied by advantage in points difference and at the same time the loser teams demonstrate the negative correlation between shot efficiency and points difference evolution. We suppose that this fact once more indicates on extreme relevancy of defensive action and particularly of goalkeeper performance for success of team in even games in Handball. Nevertheless, in order to explain the reasons of the result in some particular game it is necessary to analyze the players actions in real-time of the game and their relationship with the activity of opposite team.